Using Small Group Discussions to Examine Students' Perceptions of Recount Text - Jilan Fisabilillah Haya Wina; Wahyudin Fitriyana; Sumarta Sumarta (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The purpose of this study is that students are involved in learning reading comprehension through small group strategies in class reading and to find out students' perceptions of learning reading comprehension through small group strategies. This research is a qualitative descriptive design with a case study method. Participants in this study were all students of class VII A SMPN 5 Karawang, and 5 students were interviewed. The data collection technique that the authors use is observation to observe student behavior during learning to read comprehension using small group techniques. In addition, the writer also uses semi-structured interviews to find out students' perspectives in learning reading comprehension using small groups. The data that has been obtained is analyzed using a qualitative technique proposed by Miles & Huberman. The analysis consists of three activity flows, namely: data reduction, data presentation, drawing conclusions/verification. The results showed that students find it helpful to learn reading comprehension with small group strategies because they collaborate with their group mates.